Local and regional founder effects in lake zooplankton persist after thousands of years despite high dispersal potential. Issue 5 (15th February 2014) - Ventura, M.; Petrusek, A.; Miró, A.; Hamrová, E.; Buñay, D.; De Meester, L.; Mergeay, J.
Abstract We reconstructed the genetic structure of a planktonic crustacean Daphnia longispina living in high mountain lakes and ponds in the Pyrenees to investigate whether it was shaped by persistent founder effects originating shortly after the last glacial maximum or by ongoing dispersal and effective migration (gene flow). We found that the genetic structure can largely be explained by a single colonization event following gradual deglaciation of the Pyrenees 10 000–15 000 years ago. Nuclear genetic diversity declined steeply from southeast to northwest, suggestive of serial colonization of available habitats with advancing deglaciation. The spatial genetic structure suggests that founder effects were major determinants of the present‐day diversity, both at the catchment level and at the level of individual water bodies, further supporting extremely low effective migration rates. This study reveals a prime example of a founder effect that is both long lasting and maintained at small spatial scales. Our data suggest a process of isolation by colonization as a result of strong priority effects and monopolization. We found evidence for the spread of haplotypes with Pyrenean ancestry across the Palaearctic over distances up to 5500 km, although the local genetic structure after colonization was hardly influenced by contemporary dispersal. Finally, our data also suggest that mitochondrial mutation rates in the studied populations were seven times higher than typically assumed. Overall, we show that founder effects can persist for centuries even at small spatial scales at which the potential for dispersal is high.